Relationship between resilience, anxiety, and social support resources among Japanese elementary school students. Issue 1 (2023) - Yamamoto, Toshie; Nishinaka, Hirofumi; Matsumoto, Yuki
Abstract: This study highlighted the factors that potentially enhance student resilience and investigated the relationship between resilience, anxiety, and social support resources among Japanese elementary school students, and highlighted the factors that enhance student resilience. Using surveys, the study provides evidence of 625 Japanese third- and fourth-grade students' potential resilience. These surveys revealed the factors that boost resilience, insightful information on gender and age differences, and the correlations between social support resources, resilience, and factors that potentially boost resilience. Our findings suggest that support systems may play an integral role in building student resilience and that factors such as family and community play a part in developing child resilience. Thus, we can expect that support systems may play a role in building student resilience, with factors such as home and community playing a role in fostering children's resilience. Moreover, resilient students are aware of available family and school support resources. This study provides directions for future research on aiding students with difficulties in developing resilience. Highlights: A survey was used to highlight factors that enhance students' potential resilience. We found a correlation between social support resources and student resilience. Family and community are key factors in the development of student resilience.